HRD Climate and Job Satisfaction of Public and Private Sector Banks - Sohal, Adeep; Venkatesan, M. (Prabandhan: Indian Journal of Management, 2016)
The globalization era, technology changes, and fierce business competition have brought in new challenges to human resource managers in organizations. The literature survey reiterates that the congenial human resource development climate motivates employees to contribute to their maximum potential and promotes job satisfaction. In line with this, the present study was designed to analyze the relationship between the human resource development climate and job satisfaction and also to study the difference in human resource development climate and job satisfaction between public and private banking professionals. A sample of 80 banking professionals in Delhi was administered with the human resource development climate scale (Rao&Abraham, 1985) and job satisfaction scale (Spector, 1994). A positive correlation was found between HRD climate and job satisfaction in both public and private banking professionals. The general climate, which is a dimension of HRD climate, and operating conditions, which is a dimension of job satisfaction, were found to be significantly different between public and private banking professionals.